2020
DOI: 10.48550/arxiv.2006.10481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Practices and Capabilities in API Management: A Systematic Literature Review

Max Mathijssen,
Michiel Overeem,
Slinger Jansen

Abstract: Traditional organizations are increasingly becoming software producing organizations. This software is enabling them to integrate business processes between different departments and with other organizations through Application Programming Interfaces (APIs). The main task of managing APIs is to ensure that the APIs are easy to use by third parties, such as providing helpful documentation, monitoring API performance, and even monetizing API usage. The knowledge on API management is scattered across academic lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…The full description of how this data was acquired is provided in the accompanying article [66]. The aforementioned article describes the execution of a Systematic Literature Review (SLR).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full description of how this data was acquired is provided in the accompanying article [66]. The aforementioned article describes the execution of a Systematic Literature Review (SLR).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…For example, the community engagement and lifecycle focus areas contain many practices, while monitoring is a domain consisting of a minor but relevant amount of practices and capabilities related to it. Originally, the lifecycle, community engagement, security and monitoring focus areas originate from literature and were identified as part of the systematic literature review [66] that was conducted by the authors. The performance and commercial focus areas were newly created as a result of the discussion and categorization sessions conducted among the authors, by categorizing identified capabilities and practices.…”
Section: Focus Areas and Capabilitiesmentioning
confidence: 99%
“…The initial model (v0.1) used the work of De [3] as a starting point. Next a SLR [34], based on the methodology developed by Okoli [35] and guidelines composed by Kitchenham and Charters [36], was used to further design and populate the model (resulting in version v0.2). In this SLR a comprehensive overview of literature related to…”
Section: Research Approachmentioning
confidence: 99%
“…API Management capabilities such as controlling API lifecycles, access and authentication to APIs, monitoring, throttling, and analyzing API usage, as well as providing security and documentation are often implemented through an integrated platform, which is supported by an API gateway." [22] API governance can also be seen as a combination of data and IT governance, and as a part of broader API management. There is a need for a governance model that describes the structure of how API governance should be designed and executed.…”
Section: ) Life-cycle Alignmentmentioning
confidence: 99%